Analisis Kesulitan Mahasiswa PGMI STAI AL-FALAH Banjarbaru dalam Mengembangkan RPP Bahasa Indonesia Berdiferensiasi - Hayatul Mursyida (Program Studi PGMI STAI Al Falah Banjarbaru, 2025)
This study aims to analyze the difficulties faced by students of the Islamic Elementary School Teacher Education (PGMI) Study Program at STAI Al Falah Banjarbaru in developing Indonesian Language Lesson Plans (RPP) that comply with the principles of differentiated instruction within the Merdeka Curriculum. The research method employed is descriptive qualitative with a case study approach. Data were collected through interviews, RPP document analysis, and observation of lecture activities. The results indicate that students encountered difficulties in understanding the concept of differentiated instruction, determining students' learning needs, and connecting differentiation with learning objectives and assessment. The contributing factors to these difficulties include minimal field practice experience, a lack of pedagogical literacy regarding the Merdeka Curriculum, and limited guidance in RPP preparation. This study recommends the necessity of enhancing training and implementing Project-Based Learning (PjBL) in lectures to improve the readiness of students as prospective professional teachers.